Stimulus through Insurance: The Marginal Propensity to Repay Debt - Gizem Koşar; Davide Melcangi; Laura Pilossoph; David Wiczer (Institute of Labor Economics (IZA), 2023)
Using detailed micro data, we document that households often use "stimulus" checks to pay down debt, especially those with low net wealth-to-income ratios. To rationalize these patterns, we introduce a borrowing price schedule into an otherwise standard incomplete markets model. Because interest rates rise with debt, borrowers have increasingly larger incentives to use an additional dollar to reduce debt service payments rather than consume. Using our calibrated model, we then study whether and how this marginal propensity to repay debt (MPRD) alters the aggregate implications of fiscal transfers. We uncover a trade-off between stimulus and insurance, as high–debt individuals gain considerably from transfers, but consume relatively little immediately. We show how this mechanism can lower short-run fiscal multipliers, but sustain aggregate consumption for longer.
Keywords: E21; E62; 330; marginal propensity to consume; consumption; debt; fiscal transfers